2021
DOI: 10.3389/fcell.2021.734720
|View full text |Cite
|
Sign up to set email alerts
|

Development of Extracellular Vesicle Therapeutics: Challenges, Considerations, and Opportunities

Abstract: Extracellular vesicles (EVs) hold great promise as therapeutic modalities due to their endogenous characteristics, however, further bioengineering refinement is required to address clinical and commercial limitations. Clinical applications of EV-based therapeutics are being trialed in immunomodulation, tissue regeneration and recovery, and as delivery vectors for combination therapies. Native/biological EVs possess diverse endogenous properties that offer stability and facilitate crossing of biological barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 520 publications
(844 reference statements)
0
93
0
Order By: Relevance
“…EVs, in contrast, have no vascular obstructive effect or apparent adverse effects. These properties suggest that EVs could be safely and easily used in therapies such as for respiratory diseases ( Abreu et al, 2016 ; Fujita et al, 2018 ; Claridge et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs, in contrast, have no vascular obstructive effect or apparent adverse effects. These properties suggest that EVs could be safely and easily used in therapies such as for respiratory diseases ( Abreu et al, 2016 ; Fujita et al, 2018 ; Claridge et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…These are mediated by the secretion of various cytokines and soluble factors, which in turn modulate immune cell activity and promote tissue generation. More recently, MSC-derived extracellular vesicles (EVs) have also attracted attention as therapeutic products produced by MSCs which may have potential use in tissue repair and regeneration ( Baglio et al, 2012 ; György et al, 2015 ; Chen et al, 2017 ; Claridge et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the homeostasis of the regenerative microenvironment is essential for muscle growth and development. Based on the EVs delivery system, we constructed an endogenous beneficial microenvironment and activated the protection mechanism underpinning tissue regeneration, which is a promising method [ 61 , 62 ]. Increasing evidence has shown that EVs actively regulate angiogenesis in vascular endothelial cells by acting on blood vessel formation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological and pathological conditions, exosomes can be actively secreted extracellularly by various cells including immune cells, stem cells and tumor cells, and can transport a large number of biomolecules from the parent cell to other cells, which is closely related to the pathogenesis of tumors ( Claridge et al, 2021 ; Oey et al, 2021 ; Yamada, 2021 ). Because of their small size, exosomes are able to avoid phagocytosis by mononuclear macrophages and cross the vascular wall to the extracellular matrix, they are widely present in various body fluids including blood, saliva, urine, cerebrospinal fluid, and thoracoabdominal fluid ( Clark et al, 2021 ; Leggio et al, 2021 ; Mao et al, 2021 ; Prieto-Vila et al, 2021 ).…”
Section: Detection Of Exosomesmentioning
confidence: 99%